SHARIA BANK PERFORMANCE ANALYSIS USING LINEAR MODEL BASED ON RISK-BASED BANK RATING WITH VBA (VISUAL BASIC FOR APPLICATION) - Revistya Ramadhianty, Almira
In this research, the author will analyze the performance of sharia bank’s health rating using the Risk-Based Bank Rating (RBBR) method. The model used is a multiple linear regression model to explain the relationship between financial ratios such as Non Performing Financing (NPF), Financing to Deposit Ratio (FDR), Good Corporate Governance (GCG), Return on Asset (ROA), Net Operating Margin (NOM), and Capital Adequacy Ratio (CAR) with the bank’s health score. The model that has been built will be used to apply the analysis to the bank’s quarterly financial statements. The construction of the linear model is assisted by using an application that uses the Visual Basic for Application (VBA) programming language in Microsoft Excel. The significance of the obtained parameter results from the linear model are used as an indication of anomalies in the bank's behavior in maintaining the health score. To investigate these anomalies further, a more in-depth analysis is conducted by examining the annual financial statements to provide a qualitative assessment of the sharia bank's health.